Local Evolution of pH with Time Determined by Shear Force‐based Scanning Electrochemical Microscopy: Surface Reactivity of Anodized Aluminium. Issue 10 (6th October 2016) - Etienne, Mathieu; Rocca, Emmanuel; Chahboun, Najat; Veys‐Renaux, Delphine
Abstract: Shear force‐based scanning electrochemical microscopy is applied for pH monitoring during a sealing reaction at the interface between anodized 7175 aluminium alloy and a solution containing Cr(III) and Zr(IV) species. pH measurement is carried out with the electrode positioned near enough to the surface to be in the diffusion zone of the liquid/solid interface, in the reach of the surface‐generated pH modulating chemical species. The pH electrode is accurately positioned at the surface of the metal with shear force detection before the solution is loaded into the electrochemical cell at room temperature and the pH is monitored for 20 minutes. After a rapid increase, a maximum pH is reached. A good correlation is found between this in situ measured pH and the precipitation pH of metallic species contained in the solution. Interpretation of the results from in situ pH monitoring and open‐circuit potential of the treated surface allows to propose three distinctive steps during the sealing process: an activation of the alumina layer by its dissolution during the first minutes, which induces an increase of the interfacial pH, followed by a precipitation of the sealing products as soon as the precipitation domain is reached and finally a consolidation of the sealing layer during the next 20 min. Abstract :